Kyrgyz Republic : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The Kyrgyz economy is highly dependent on remittances and foreign aid and does not have access to international capital markets. Inequality is relatively low, but poverty is widespread. The COVID crisis led to a sharp recession with output contracting by 8.6 percent in 2020, public debt rising by 16.5 percent of GDP to 68 percent, and the som depreciating by 19 percent against the USD . Under the assumption that the global pandemic begins to decisively recede this year, a rebound in growth is expected in 2021-22. However, significant uncertainty surrounds the baseline outlook and the recovery could be delayed if downside risks materialize. In the medium to long term, the main challenge is to create jobs for about 65,000 new jobseekers annually and to reduce labor out-migration. This will require deep structural reforms to transform the economy from a reliance on remittances to more diversified and private sector-led growth that is underpinned by higher investment and exports.